Hibiscus sabdariffa calyx extract protects human keratinocyte cells from fluoranthene-induced ferroptosis via the repression of aryl hydrocarbon receptor - Mani Iyer Prasanth; Dicson Sheeja Malar; Kanika Verma; Anchalee Prasansuklab; Tewin Tencomnao (Ecotoxicology and Environmental Safety)
Polycyclic aromatic hydrocarbons (PAHs) commonly associated with fine particulate matter (PM2.5) is gaining global concern because of their diverse biological toxicity. Fluoranthene (Flu) is a low molecular weight PAH and is reported to induce carcinogenicity, cardiotoxicity and skin damages. Currently, there are no effective treatment strategies to protect the host from PAHs, rather than avoiding the PAH exposure. The understanding of the impact and molecular mechanism of Flu toxicity on keratinocytes as well as effective protective mechanisms against the toxic outcomes remain limited. Herein, we explored the protective mechanism of Hibiscus sabdariffa (HS) calyxes ethanol extract against Flu toxicity in human keratinocyte HaCaT cells. In this study, biochemical assays, fluorescent microscopic imaging, real time PCR, western blot and in silico molecular docking analyses were employed. We found that pre-treatment of HS could restore Flu-induced reduction in cell viability through the inhibition of oxidative stress, augmenting antioxidant mechanism, modulation of aryl hydrocarbon receptor (AhR), constitutive androstane receptor (CAR)/pregnane X receptor (PXR)-mediated activation of phase I and II metabolism genes. Furthermore, the Flu-induced altered expression of gluconeogenesis-associated genes (G6PASE, PEPCK) and inhibition of ER-α expression were reversed with HS pre-treatment. The constituents of HS including pelargonidin 3-rhamnoside 5-glucoside, 7-methoxyisoflavone and 7,8-dihydroxycoumarin were identified to have phytoestrogenic potential as determined by docking analysis. Interestingly, our data also revealed for the first time the involvement of ferroptosis in Flu-induced keratinocyte cell death, which could be observed through the downregulation of FTH1, GPX4 and SLC7A11 protein expression upon Flu exposure, while the pre-treatment with ferroptosis inhibitor Ferrostatin-1 or HS extract significantly restored those changes. Overall, this present work highlights the harmful impact of Flu on human keratinocytes and underscores the potential of Hibiscus sabdariffa calyx extract as a natural source of protective agents against Flu-induced skin cytotoxicity, particularly through the repression of nuclear xenobiotic receptors and the attenuation of ferroptosis.